Carbon Footprint and Environmental Hotspot Analysis of Public Textbook Procurement: Evidence from the Federal Ministry of Education, Abuja, Nigeria - Usman Abdulrasheed (RESEARCH JOURNAL OF PURE SCIENCE AND TECHNOLOGY, 2026)
Public procurement is increasingly recognised as a strategic instrument for advancing environmental sustainability; however, limited empirical evidence exists on the environmental impacts of procurement operations in developing countries. This study assessed the carbon footprint and environmental hotspots associated with the FY2023 basic and secondary school textbook procurement cycle at the Federal Ministry of Education, Abuja, Nigeria, using a gate to-gate Environmental Life Cycle Assessment (ELCA) approach. The assessment followed the ISO 14040/14044 framework, covering procurement planning, tender advertisement and bid submission, bid evaluation, and contract award, while excluding upstream production and downstream use and disposal stages. Primary data were obtained through procurement records, structured inventory sheets, direct observation, and key informant interviews, while carbon emissions were estimated using the activity data–emission factor approach. The results revealed that the procurement cycle generated a total carbon footprint of 24,852.10 kgCO₂e. Paper consumption was the dominant emission source, contributing 14,875.25 kgCO₂e (59.9%), followed by fuel consumption with 6,882.60 kgCO₂e (27.7%), waste disposal with 2,581.65 kgCO₂e (10.4%), electricity consumption with 500.00 kgCO₂e (2.0%), and transportation with 12.60 kgCO₂e (0.1%). The tender advertisement and bid submission stage was identified as the principal environmental hotspot due to intensive documentation and administrative activities. The study concludes that integrating ELCA into public procurement can strengthen sustainable procurement practices by identifying carbon-intensive activities and informing evidence-based interventions, including digital procurement, reduced paper documentation, improved energy management, and environmentally responsive procurement policies within Nigeria's public sector.